UPAYA PENINGKATAN DISIPLIN IBADAH MELALUI PEMBIASAAN SALAT JAMAAH DI MASJID PADA SISWA DI SDIT DARUL-FIKRI KECAMATAN ARGAMAKMUR KABUPATEN BENGKULU UTARA - Muhammad Thohir (UIN Fatmawati Sukarno Bengkulu, 2016)
This research is motivated by the fact that (1) the state of society in general has not fully perform prayers in themosque, making it difficult to inculcate the habit of public prayers for students, (2) The trend behavior of primary schoolstudents in general are playing around and joking, so unruly to order in worship, and (3) the students made up of diverseenvironments and habits at home, there are familiar congregational prayers some are not used to. The purpose of thisstudy was to determine the depth of the measures applied in the habituation efforts Integrated Islamic Elementary School(SDIT) Darul Fikri Argamakmur in public prayers in the students and the achievements seen from the behavior of thestudent prayer. This study used a qualitative method with descriptive approach. The collection of data through observation,interviews, and document analysis. Testing the validity of the data through continuous observation and triangulation ofsources and methods. Presentation of the results and analysis of data using interactive models, include: data collection, datareduction, data presentation, and conclusion. The results of this study indicate that: (1) The efforts of habituation publicprayers in Integrated Islamic Elementary School (SDIT) Darul Fikri Argamakmur done by incorporating activities habituationcongregational prayers in the curriculum as a basic framework of routines and learning, and establish measures such asscheduling clerk prayer pilgrims, making Kultum schedule, schedule security officer, complete the facilities of the mosque,providing infaq box, and make a deposit program rote. (2) The results achieved by Integrated Islamic Elementary School(SDIT) Darul Fikri Argamakmur in public prayers familiarize students is 80% of parents are satisfied with the increase inreligious discipline their children.